A companion to the theology of John Mair - Slotemaker, John T.; Witt, Jeffrey C. (Brill's companions to the Christian tradition ;, 2015)
The Companion to the Theology of John Mair explores the theological thought of this significant sixteenth-century Parisian scholar. It includes articles exploring his positions on humanism and scholasticism, faith and theology, Trinity and Incarnation, Ethics and Casuistry, Justification and Sacraments.